Cost Recovery, Equity, and Efficiency in Water Tariffs Evidence From African Utilities - Ying, Yvonne (The World Bank, 2010)
Water and sanitation utilities in Africa operate in a high-cost environment. They also have a mandate to at least partially recover their costs of operations and maintenance (O&M). As a result, water tariffs are higher than in other regions of the world. The increasing block tariff (IBT) is the most common tariff structure in Africa. Most African utilities are able to achieve O&M cost recovery at the highest block tariffs, but not at the first-block tariffs, which are designed to provide affordable water to low-volume consumers, who are often poor. At the same time, few utilities can recover even a small part of their capital costs, even in the highest tariff blocks. Unfortunately, the equity objectives of the IBT structure are not met in many countries. The subsidy to the lowest tariff-block does not benefit the poor exclusively, and the minimum consumption charge is often burdensome for the poorest customers. Many poor households cannot even afford a connection to the piped water network. This can be a significant barrier to expansion for utilities. Therefore, many countries have begun to subsidize household connections. For many households, standposts managed by utilities, donors, or private operators have emerged as an alternative to piped water. Those managed by utilities or that supply utility water are expected to use the formal utility tariffs, which are kept low to make water affordable for low-income households. The price for water that is resold through informal channels, however, is much more expensive than piped water